Primates (Symphalangus syndactylus syndactylus, Macaca nemestrina, Macaca fascicularis) Population in the Ape Park Tourist Area Forest for Special Purpose of Aek Nauli - Barus Johni Arisantana; Hidayat Jafron Wasiq; Maryono Maryono (E3S Web of Conferences, 2018)
Forest for special purpose of Aek Nauli is an highland rainforest as habitat for primates and tourism area in Marsose, Sibaganding Village, Simalungun, Lake Toba Geopark in North Sumatra. As an endangered and protected species, siamang (Sympalangus syndactylus syndactylus) in the same habitat as pig-tailed macaque (Macaca nemestrina) and long-tailed macaque (Macaca fascicularis). Nowadays, the siamang population is declining due to the conversion of forest to non-forests, forest fragmentation and illegal trade. Long-tailed macaque and pig-tailed macaque are agricultural pests that are economically harmful to communities around the forest. The primate population data is needed as input for the sustainable management strategy by stakeholders to further preserve forest areas and primate populations. This study was carried out for 3 months from May to July 2018. To determine the number of primate populations performed by the concentrated area method. Estimates of primate populations are: A. Siamangs; 1 group with 3 individuals, population size 0.06. Age structure of population 1 juvenile 1, 2 adults. B. Pig-tailed macaque; 3 groups with 65 individuals, population size 1.1. The age structure is 17 tillers, 17 adolescents and 31 adults. C. Long-tailed macaque; 3 groups with 23 individuals, population size 0.5. Age structure of 5 tillers, 7 adolescents and 11 adults.